Case Report: Articular Gout in Four Dogs and One Cat - Kim, Hyo-Sung; Hwang, Hyun-Jeong; Kim, Han-Jun; Do, Sun Hee (Frontiers in Veterinary Science, 2022)
Background: There is widespread prejudice in veterinary medicine that gout does not occur in non-human mammalians. However, we recently discovered monosodium urate crystals in the synovial fluid obtained from a few dogs and a cat. Since it is the definitive and gold standard to diagnose gout, we report these cases as newly emerging diseases in companion animals. Case presentation: Four dogs and one cat were presented at our hospital because of lameness due to an unknown cause. Even after the routine examinations, including radiographic imaging, laboratory examination, and arthrocentesis, we were unable to find a clear cause of polyarthritis. However, we later discovered monosodium urate crystals in the synovial fluid of the animals, confirmed by polarized microscopy. In one of the two dogs treated with immunosuppressants, the disease relapsed, and the other did not show any symptoms for 3 months. The other two dogs were treated with xanthine oxidase inhibitor, where one died, and the other did not show any symptoms for 3 years. The cat was treated with drainage and intra-articular dexamethasone injection, but the disease recurred after 6 months. Conclusion: This is the first report to confirm that articular gout can occur in dogs and cats. Care must be taken not to neglect needle-shaped materials in the synovial fluid. Gout should also be included in the differential diagnosis of arthritis and further research is needed in these animals.